Cosmic perspectives: an astronomical narratoscope at boyden observatory used to interpret borrowed moments from indigenous cosmology - Bester, Leon (University of the Free State, 2021)
Abstract not available
Dissertation (M.Arch. (Architecture))--University of the Free State, [2021]
Keywords: Cosmic perspectives; Poetry of science; Relationship - Science and poety; Indigenous cosmology